Development of fat-holding and drug-eluting implant for breast-conserving surgery (Transactions on Additive Manufacturing Meets Medicine, 2023)
Breast conserving surgery (BCS) is a standard treatment for breast cancer, aimed at removing tumours whilst preserving as much of the healthy breast tissue as possible. However, the surgical procedure often leaves a noticeable dent at the surgery site and necessitates subsequent radiotherapy to minimise cancer reoccurrence risk. This presents a significant aesthetic and therapeutic challenge, prompting demand for effective post-BCS partial breast reconstruction. Traditional reconstruction approaches, such as autologous fat injection, suffer from substantial fat loss (40-60%) to the surrounding tissue, resulting in suboptimal outcomes [1].To address these issues, a novel biodegradable breast implant with the capacity to elute anti-cancer drugs is proposed. The contour of this implant is customised based on MRI-derived dimensions of the excised tumour and adjacent healthy tissue from individual patients. For modelling and design simplification, a spherical tumour with a 20 mm diameter is utilised as the model. Lattice designs for the implant were explored using FLatt Pack, an open-source software enabling the addition of lattice infill to the 3D model [2]. The triply periodic minimal surface (TPMS) gyroid lattice was chosen for its interconnectivity of internal pores and good permeability [3]. 3D models with a range of dimension-to-cell ratios (from 20:1 to 5:1) were generated and printed by LCD printing.To evaluate the implant's fat holding capability, a solution mimicking adipose tissue, composed of 7.5% w/v xanthan gum in water with blue colouring, was prepared. The solution was injected into a silicone mould containing the implant, to evaluate the permeation, injection resistance, and fat holding capacity. Of the examined samples, the dimension-to-cell ratios of 10:1 showed the best permeation of fat and the lowest injection resistance. Evaluation of drug incorporation into the bioresorbable scaffold to enable the drug eluting function of the implant is ongoing.Author’s statementConflict of interest: Authors state no conflict of interest. Animal models: No animal experiments were performed. Informed consent: No need for informed consent was required for this study. Ethical approval: No need for ethical approval was required for this study. Acknowledgments: We would like to thank Prof. Jerome Pereira and Prof. Sue Down at James Paget University Hospitals, Great Yarmouth, UK, for their clinicl expertise in breast cancer surgery and contribution to implant desgins.Research funding: This project was funded by UEA PVC impact fund and UEA Health and Social Care Partners.References[1] A. Kochhar, I. Wu, R. Mohan, A. Condé-Green, A.T. Hillel, P.J. Byrne, J.H. Elisseeff, A comparison of the rheologic properties of an adipose-derived extracellular matrix biomaterial, lipoaspirate, calcium hydroxylapatite, and cross-linked hyaluronic acid, JAMA Facial Plast Surg. 16 (2014) 405–409. https://doi.org/10.1001/jamafacial.2014.480.[2] I. Maskery, L.A. Parry, D. Padrão, R.J.M. Hague, I.A. Ashcroft, FLatt Pack: A research-focussed lattice design program, Addit Manuf. 49 (2022). https://doi.org/10.1016/j.addma.2021.102510.[3] J. Santos, T. Pires, B.P. Gouveia, A.P.G. Castro, P.R. Fernandes, On the permeability of TPMS scaffolds, J Mech Behav Biomed Mater. 110 (2020). https://doi.org/10.1016/j.jmbbm.2020.103932.
Keywords: Lattice; Gyroid; breast conserving surgery; Biodegradable implants